PENGARUH PENAMBAHAN TANAMAN BERUAS LAUT (Scaevola taccada) DALAM PEMBUATAN BIOPLASTIK DARI Kappaphycus alvarezii - Norhayati, Syarifah; Melati, Melati; Jumsurizal, Jumsurizal (Marinade, 2021)
The manufacture of bioplastics from kappapycus alvarezii with the addition of extraction of the plant clade, the sea (Scaevola taccada). This study examines the influence of the addition of extracts of the plant clade, the sea and the concentration of carrageenan on physical and mechanical characteristics of bioplastics.The variables studied is the addition of the amount of carrageenan 2 g, 1.5 g, and 1 g with plant extracts clade, sea 0%, 2.5% and 5%. The results obtained from the manufacture of bioplastics to the thickness of the highest in treatment F1, namely 0.393 mm, for all the thickness of the average range 0.0320-0.393 mm. The level of solubility of the most high are in treatment F1 that is 20,92 minutes, for an average of all the solubility range 12.59-20.92 minutes. The rejection and death of the insects was highest in treatment F3, 7% and 3% with the addition of a leaf segmented sea (Scaevola teccada). Thus the addition of the clade, the sea can be said to not meet the Japanesse Industrial Standard (JIS) in the determination of the thickness of the bioplastic that is good that is equal to â‰¤ 0.25 mm and also for solubility do not meet the SNI to the water resistance of 99%.